The Effect of Using Pazopanib With Food vs. Fasted on Pharmacokinetics, Patient Safety, and Preference (DIET Study). Issue 5 (9th July 2019) - Lubberman, Floor J.E.; Gelderblom, Hans; Hamberg, Paul; Vervenne, Walter L.; Mulder, Sasja F.; Jansman, Frank G.A.; Colbers, Angela; van der Graaf, Winette T.A.; Burger, David M.; Luelmo, Saskia; Moes, Dirk Jan A.R.; van Herpen, Carla M.L.; et al.
Abstract : Pazopanib is taken fasted in a fixed oral daily dose of 800 mg. We hypothesized that ingesting pazopanib with food may improve patients' comfort and reduce gastrointestinal (GI) adverse events. Therefore, we investigated the bioequivalent dose of pazopanib when taken with food compared with 800 mg pazopanib taken fasted. In addition, we investigated the differences in GI toxicity, patient satisfaction, and patient's preference for either intake. The intake of 600 mg pazopanib with food resulted in a bioequivalent exposure and was preferred over a standard pazopanib dose without food. No differences were seen in GI toxicities under both intake regimens. Patients seem to be more positive about their feelings about side effects and satisfaction with their therapy when pazopanib was taken with food. Forty‐one of the patients (68%) preferred the intake with a continental breakfast.